Fish biodiversity and livelihood of fishermen at an Oxbow lake of South-West Bangladesh - Jamil, -; Sharif, BM Newaz; Abit, Lirong Yu; Miah, Md Idris; Shahjahan, Md (Asian Journal of Medical and Biological Research, 2022)
The present study was conducted to know the biodiversity status and assess the existing livelihood conditions of the fishers of Habullah Baor at Bagherpara upazila, Jashore district from November 2017 to April 2018. Sixty fishermen were randomly selected for collecting data through a semi structured questionnaire. The current study discovered that there were 11 different fish species from six orders and seven families in the Habullah baor. All of the sampled fishermen were Hindu. About 25% of the fishermen was young aged, majority was middle aged and 25% was old aged group. A total of 75% of the fishermen had nuclear family and 25% families lived in joint family. Among the fishermen 85% had a few decimal of cultivable land and 15% were truly landless. Annual income of the respondents varied from 30,000 to 70,000 BDT with an average of 42,833 BDT. All fishers had access to drinking water from tube wells. Most of the fishers lived in katcha houses. About 15% of the fishers enjoyed electricity facilities in their home. Among the fishermen investigated, majority had earthen latrine, 20% used tin shed latrine, 8% used concrete latrine and a few of them 10% had no latrine. There were no modern medical facilities in the villages. The respondents had no alternate income sources during the dry season and at the time of ban period. The fishers as a whole are leading measurable life due to great financial hardship. Proper conservation and management measures can be taken to enhance the availability of fish fauna in Habullah baor, so that, the fishermen can harvest ample fish on sustainable basis. Asian J. Med. Biol. Res. 2022, 8 (3), 165-180